Dimensions of the health benefits of wellness tourism: A review - Liao, Chenmei; Zuo, Yifan; Xu, Shaogui; Law, Rob; Zhang, Mu (Frontiers in Psychology, 2023)
The benefits of wellness tourism have been recently noted by researchers and industry representatives. This study examined the health dimensions of these benefits posited by a large array of interdisciplinary studies from 2002 up to the present. Open coding was used to conduct an inductive evaluation to classify these health benefits. Results showed four main dimensions, namely, physical fitness, psychological fitness, quality of life (QOL), and environmental health; however, these dimensions need further investigation. Physiological health benefits can also be demonstrated through future experiments, which can further focus on empirical research on the psychological benefits and its overall effect on the QOL. This study contributes to the current literature by providing novel theoretical foundations and subsequently aids practitioners to understand customers better and convey their marketing messages to tourists more effectively.